Content Matters: How Information Literacy Workshops Tailored for Marginalized Groups Can Impact Student Performance - Ball, Heather F. (Evidence Based Library and Information Practice, 2025)
Objective – This study sought to understand information literacy instruction tailored for first-year students of color in higher education, and the impact of that instruction on student performance and confidence levels.Methods – The study was conducted at a four-year doctoral-granting higher education institution and was designed as a QUAL+quan convergent mixed-methods study. It utilized critical race theory (CRT) as its theoretical framework, a participatory action research (PAR) approach for its design, and critical pedagogical practices to tailor the instructional content and delivery. The instruction was designed as a multi-session information literacy workshop series delivered outside of the traditional classroom and was comprised of six one-hour sessions: an initial focus group, four information literacy sessions focusing on specific aspects of the research process, and semi-structured interviews.Results – Data collected through discussions, open-ended activities with rubrics, and pre- and post-series surveys were analyzed to determine whether the instructional series impacted student learning outcomes. The results showed the series had a positive impact on student performance and their confidence levels pertaining to understanding and applying information literacy concepts.Conclusion – The study is significant as it is the first to specifically utilize CRT and PAR in a multi-session information literacy workshop series for first-year students of color delivered outside of the traditional classroom setting and can serve as a model for other institutions.